2002
DOI: 10.1111/j.1744-7410.2002.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Populations of the European freshwater pulmonate Physa acuta are not reproductively isolated from American Physa heterostropha or Physa integra

Abstract: Abstract. It has long been speculated that Physa acuta, a pulmonate snail widespread and invasive in fresh waters of the old world, may have originated in North America. But the identification of a new‐world cognate has been complicated by the confused systematics and taxonomy of the Physidae in America. More than 40 species of physids are currently recognized in the United States, many with variable and overlapping morphology. We have previously established that premating reproductive isolation is negligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 36 publications
4
95
0
3
Order By: Relevance
“…As a consequence, population size is likely to vary dramatically through time because of drying out events or floods (reviewed in Städler and Jarne, 1997). Second, P. acuta is the commonest species in isolated habitats (ie ponds) of the area studied here (reviewed in Henry, 2002), in accordance with its invasive status (Dillon et al, 2002;Bousset and Jarne, unpublished data). As colonization has been shown to be associated with founding events in freshwater snails (Charbonnel et al, 2002;Meunier et al, 2004), this opens opportunities for selfing as a RA strategy.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…As a consequence, population size is likely to vary dramatically through time because of drying out events or floods (reviewed in Städler and Jarne, 1997). Second, P. acuta is the commonest species in isolated habitats (ie ponds) of the area studied here (reviewed in Henry, 2002), in accordance with its invasive status (Dillon et al, 2002;Bousset and Jarne, unpublished data). As colonization has been shown to be associated with founding events in freshwater snails (Charbonnel et al, 2002;Meunier et al, 2004), this opens opportunities for selfing as a RA strategy.…”
Section: Introductionmentioning
confidence: 93%
“…Those events might have indeed been the ecological factors maintaining selfing as a RA mechanism. Founding events very likely occur in P. acuta since this species displays high dispersal abilities (reviewed in Henry, 2002) and is the most successful worldwide invasive freshwater snail (Dillon et al, 2002;Bousset and Jarne, unpublished data). Such founding events might be scarce in the studied area, since neither demographic, nor genetic signatures were detected (Henry, 2002;Bousset et al, 2004).…”
Section: Tests Of the Rahmentioning
confidence: 99%
“…For example, P. acuta is considered a poor competitor (Brown, 1982;Perrin, 1986;Jokinen, 1987) despite its high grazing effectiveness (e.g., Lowe and Hunter, 1988;Lombardo, 2001; but see Wojdak and Mittelbach, 2007) and success in productive habitats at both local/regional (e.g., Girod et al, 1980, and authors' personal observations) and global scale (Dillon et al, 2002). P. acuta's high activity and quick response to food may translate into a high potential to exploit food, which may be exacerbated by its fast way of moving around (thus increasing access to food patches: Lombardo and Cooke, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…All species are herbivorous on periphyton and/or detritus (Brown, 2001;Lombardo and Cooke, 2002;Mouthon and Daufresne, 2008); bithyniids and valvatiids may also filter-feed on suspended particles (Kabat and Hershler, 1993;Mouthon and Daufresne, 2008). Nomenclature follows Dillon et al (2002) for Physa (= Physella) acuta and Bank (2007) for all other species.…”
Section: Study Organismsmentioning
confidence: 99%
“…Here, we investigated the dispersal vectors used by a small invasive snail, Physa (Costatella) acuta Draparnaud, 1805 (recent synonyms: Haitia acuta, Physella acuta) (Gastropoda; Pulmonata; Physidae). Other synonyms for this species are Physa heterostropha and Physa integra, as previous work has indicated that these all belong to a single widespread species (Dillon et al, 2002). Described as P. acuta from Europe, it was discovered that this species originates from North America and was probably introduced via the aquarium trade or by the intentional introduction of water plants.…”
Section: Introductionmentioning
confidence: 99%